2013
DOI: 10.1080/17470218.2012.729068
|View full text |Cite
|
Sign up to set email alerts
|

Hebbian learning for olfactory sequences

Abstract: The present paper explores the generality of the Hebb repetition effect to the learning of olfactory sequences in order to assess commonality of memory functioning across sensory modalities. Participants completed a serial order reconstruction task comprising sequences of four olfactory stimuli. Following presentation of each sequence, participants were represented with the odours and required to reconstruct their order of presentation. Surreptitious representation of the repeated sequence occurred on every th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 25 publications
6
22
2
1
Order By: Relevance
“…The structure of our Hebb repetition learning paradigm is consistent with that reported for a range of previous studies (e.g. Horton et al, 2008;Johnson et al, 2013). A 2x10x6 within-participants design was adopted, where the first factor refers to sequence type Both the filler and Hebb sequences were determined via the random generation of the numbers 1-6 (with these numbers corresponding to the left hand digitus quartus, the left hand digitus thertius, the left hand digitus secondus, the right hand digitus secondus, the right hand digitus thertius, and the right hand digitus quartus, respectively).…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…The structure of our Hebb repetition learning paradigm is consistent with that reported for a range of previous studies (e.g. Horton et al, 2008;Johnson et al, 2013). A 2x10x6 within-participants design was adopted, where the first factor refers to sequence type Both the filler and Hebb sequences were determined via the random generation of the numbers 1-6 (with these numbers corresponding to the left hand digitus quartus, the left hand digitus thertius, the left hand digitus secondus, the right hand digitus secondus, the right hand digitus thertius, and the right hand digitus quartus, respectively).…”
Section: Methodssupporting
confidence: 77%
“…Horton et al, 2008;Johnson et al, 2013). Indeed, the learning gradient for our tactile stimuli (.031) is broadly similar to that reported, for example, with verbal stimuli (=.028, under conditions of full stimulus overlap, Page et al, 2013), unfamiliar-faces (=.034, Horton et al, 2008 and odours (=.024, Johnson et al, 2013).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…One speculative explanation for this observation is that gustatory memory operates qualitatively differently to that of other stimulus modalities. Indeed, previous work from our laboratory (Johnson & Miles, 2009;Johnson, Cauchi & Miles, 2013) has demonstrated that the serial position function for olfactory memory differs to that observed for the visual and auditory domains. These differences might suggest the existence of an olfactory-specific slave system within working memory (Andrade & Donaldson, 2007), and the present data perhaps point towards similar dissociation for gustatory memory.…”
Section: Discussionmentioning
confidence: 99%
“…Farrell & Lewandowsky, 2004;Guérard & Tremblay, 2008). Finally, the Hebb repetition effect, the gradual improvement in order memory following surreptitious representation of a sequence (Hebb, 1961), is present across a range of stimuli types including, for example, unfamiliar faces (Horton, Hay, & Smyth, 2008), the spatial position of dots (Couture & Tremblay, 2006), odours (Johnson, Cauchi, & Miles, 2013), and tactile stimuli (Johnson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%